2017
DOI: 10.1038/s41598-017-04036-6
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and overexcretion of uric acid increase the risk of simple renal cysts in type 2 diabetes

Abstract: Previous studies have discussed the relationship between simple renal cysts (SRC) and serum uric acid level in healthy individuals. We performed a cross-sectional study to evaluate the association between serum uric acid level and fractional excretion of uric acid (FEUA) and simple renal cysts in males and postmenopausal females with type 2 diabetes. The overall prevalence of SRC was 18.1% in our population. SRC prevalence was significantly higher in hyperuricemic than normouricemic subjects (27.3% vs. 16.8%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 26 publications
(43 reference statements)
2
23
1
Order By: Relevance
“…In addition, Hasegawa et al (2013) reported an increased prevalence of SRCs in patients with gout, indicating that gout might be related to the formation of SRCs. For patients with T2DM, gender, age, hyperuricaemia, proteinuria, and hyperuricaemia excretion score are independent risk factors for renal cysts (Han et al, 2017). However, in addition to these factors, CVD, an increased serum phosphorus level, and reduced renal function were identified to be associated with SRCs in the present study.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In addition, Hasegawa et al (2013) reported an increased prevalence of SRCs in patients with gout, indicating that gout might be related to the formation of SRCs. For patients with T2DM, gender, age, hyperuricaemia, proteinuria, and hyperuricaemia excretion score are independent risk factors for renal cysts (Han et al, 2017). However, in addition to these factors, CVD, an increased serum phosphorus level, and reduced renal function were identified to be associated with SRCs in the present study.…”
Section: Discussioncontrasting
confidence: 54%
“…with a study that reported no association between hypertension and SRCs in diabetic patients (Han et al, 2017). In the diabetic population, the relationship between hypertension and SRCs was not significant.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…RC, especially simple RC, are lesions that are usually benign asymptomatic and are frequently observed in adults [20]. RC are more common in males [21] and are associated with hyperuricemia [22], hypertension [15,20], and renal dysfunction [23]. RC share some similar characteristics with KSD, but little is known about their specific relationship.…”
Section: Homa2-ir (>1)mentioning
confidence: 99%
“…Estimations of uric acid values are usually based on the measurements of serum uric acid concentration, uric acid clearance, and 24-h urinary uric acid excretion. A normal uric acid level, urinary concentrations, in the urine varies from 250 to 750 mg per 24 h [ 8 ].…”
Section: Introductionmentioning
confidence: 99%